2021
DOI: 10.1155/2021/6646963
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Hydroalcoholic Extract of Stachys pilifera on Oxidant-Antioxidant Status in Renal Ischemia/Reperfusion Injuries in Male Rats

Abstract: Background. Renal ischemia-reperfusion (I/R) has a pivotal role in the progression of acute renal failure. Reactive oxygen species are considered the major constituents involved in the biochemical and pathophysiological changes that were shown during kidney I/R. The purpose of this study was to examine the renoprotective effects of Stachys pilifera ethanolic extract on oxidant-antioxidant status in renal I/R-injuries in male rats. Material and methods. Twenty-one male Wistar rats were arbitrarily distributed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Extreme evaluation of ROS gives on to construction of cytotoxic metabolites which can induce irreversible disorders like damage of DNA, Peroxidation of lipid. These changes were in agreement with the worsening of kidney function, signifying that renal I/R( Ischaemia\Reperfusion)induced kidney ROS formation, reduced the capacity of cells to get rid of ROS, augmented endogenous antioxidant depletion, and deteriorated renal injury [7]. Glyphosate (N-phosphonomethyl [glycine], is an organophosphorus compound with herbicide properties discovered in 1970.…”
Section: Introductionsupporting
confidence: 60%
“…Extreme evaluation of ROS gives on to construction of cytotoxic metabolites which can induce irreversible disorders like damage of DNA, Peroxidation of lipid. These changes were in agreement with the worsening of kidney function, signifying that renal I/R( Ischaemia\Reperfusion)induced kidney ROS formation, reduced the capacity of cells to get rid of ROS, augmented endogenous antioxidant depletion, and deteriorated renal injury [7]. Glyphosate (N-phosphonomethyl [glycine], is an organophosphorus compound with herbicide properties discovered in 1970.…”
Section: Introductionsupporting
confidence: 60%
“…Oxidative stress reduces -SH reserves by oxidizing the -SH groups into disulfide or sulfonic acid. References [ 43 , 44 ]. Furthermore, the relationship between a decrease in GSH and an increase in ROS in the BLM-induced pulmonary fibrosis animal model has been confirmed [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed herein, anti-inflammatory [ 39 ], nephroprotective [ 26 , 47 ], antimicrobial [ 32 , 33 ], antioxidant [ 26 , 32 , 33 ], hepatoprotective [ 44 , 45 ], and anticancer [ 25 ] activities of the S. pilifera were confirmed in some studies. However, there are no biological studies on the ethnomedicinal use of S. pilifera with antitussive and antiasthmatic and analgesic activities, which needs more experimental data.…”
Section: Conclusion and Perspectivementioning
confidence: 84%
“…Renoprotective effects of the ethanolic extract of S. pilifera against renal ischemia/reperfusion damage in rats were described by Moslemi et al, and they found that the extract (500 mg/kg) significantly reduced the renal injury in the ischemia/reperfusion model, possibly by improving some renal function indicators, restoring thiol group storage, and preventing protein oxidation. It appears that the S. pilifera extract exerts renoprotective effects against renal ischemia/reperfusion, possibly by improving the oxidant-antioxidant status [ 47 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%